2022
DOI: 10.1038/s41598-022-05197-9
|View full text |Cite
|
Sign up to set email alerts
|

Matrix enrichment by black phosphorus improves ionization and reproducibility of mass spectrometry of intact cells, peptides, and amino acids

Abstract: Intact (whole) cell matrix-assisted laser desorption/ionization mass spectrometry (MALDI-TOF MS) is an established method for biotyping in clinical microbiology as well as for revealing phenotypic shifts in cultured eukaryotic cells. Intact cell MALDI-TOF MS has recently been introduced as a quality control tool for long-term cultures of pluripotent stem cells. Despite the potential this method holds for revealing minute changes in cells, there is still a need for improving the ionization efficiency or peak re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Interactions of the analytes with nanostructured substrates may affect LDI-MS efficiency, and they can be characterized by complementary analytical techniques. A good example of such work was reported by Mandal et al [26].…”
Section: Ldi-ms Performances Of Silver Nanostructures For Lipidsmentioning
confidence: 85%
“…Interactions of the analytes with nanostructured substrates may affect LDI-MS efficiency, and they can be characterized by complementary analytical techniques. A good example of such work was reported by Mandal et al [26].…”
Section: Ldi-ms Performances Of Silver Nanostructures For Lipidsmentioning
confidence: 85%
“…BP has been used as a matrix in LDI-MS for detection of various compounds. 20,21 It has also been reported that elemental phosphorus itself can generate phosphorus clusters under laser ablation. [22][23][24][25] This inspired us to use LDI-MS to resolve the puzzle of the BP degradation mechanism.…”
Section: Introductionmentioning
confidence: 99%